Nitrogen-rich covalent organic polymers for efficient solid phase extraction of nonsteroidal anti-inflammatory drugs from water samples - Yuqi Cheng; Jia Li; Xiaochen Xiu; Xinghua Teng; Wen Zhang; Lei Ji; Leilei Wang (Advances in Sample Preparation)
Non-steroidal anti-inflammatory drugs (NSAIDs) have received increasing attention owing to their ubiquitous occurrence in environmental water systems and adverse effects. In order to monitor trace levels of NSAIDs from complex water samples, development of facile and efficient sample pretreatment is of great significance. Herein, a nitrogen-rich covalent organic polymer containing phenyl, triazine and amine groups was fabricated via solvent-free copolymerization. Then, utilizing nitrogen-rich covalent organic polymer as adsorbent for solid phase extraction cartridges, the pretreatment method was combined with high-performance liquid chromatography-diode array detection to quantify five representative NSAIDs (ketoprofen, carprofen, flurbiprofen, diclofenac and mefenamic acid) in environmental water samples. Under the optimal extraction conditions (adsorbent amount: 40 mg; NaCl concentration: 0%; pH 6; extraction time: 20min; eluent solvent: 4 mL of formic acid/acetonitrile (5%, v/v)), the proposed method provided low detection limits (0.06–0.2 μg L-1), wide linear ranges (0.2–100 μg L-1) with correlation coefficients (0.9991–0.9997) and acceptable precision (RSDs, 6.6–8.5% for intra-day, 7.2–9.5% for inter-day). The practical application of the method was confirmed through the successful determination of NSAIDs in tap water, surface water, and sewage. The recoveries in these samples at the four NSAIDs concentration levels ranged from 81.3% to 109.8%, with the RSDs lower than 7.8%.